O direito constitucional de reunião entre textos e ruas - Brito, Gilton Batista (2016)
The dissertation presents several texts dealing with the freedom of assembly in international human rights law, foreign law and the Brazilian constitutional law. It is not mere reproduction of normative statements, includes research the legal discourse developed around that fundamental freedom by doctrine and jurisprudence in the various protection systems, while making a critical reflection, as befits academic research. This bias is related to the perspective of legal effect. On the other hand, from the perspective of social effectiveness, by intuitively notice the growing recurrence to the use of public space from the streets as a form of collective action with extensive diversity of repertoire and considerable consequences, academic study presents several episodes related to the demonstrations in Brazil and other countries illustrative for illustrative and representative title. The purpose is to understand the limits and possibilities of this fundamental freedom, closely linked to the development of democracy.________________________________________________________________________________________________________________________________